(untitled) (Academicia Globe: Inderscience Research, 2023)
It is well-known that just as the Father begins with the cradle, the beginning of education from the cradle, even before the birth of a child, will result in future results. Preschoolers currently working in our country have claimed responsibility for providing early education to young people in our country. Up to the end of the school year, the form of knowledge in schools is an exercise. (Matthew 24:14; 28:19, 20) Jehovah’s Witnesses would be pleased to discuss these answers with you.